Openness to Disappointment: The Role of the Subject in Gadamer’s Hermeneutics - Steinmann, Michael (Ekstasis: Revista de Hermenêutica e Fenomenologia, 2013)
DOI: http://dx.doi.org/10.12957/ek.2013.7366 The paper concerns the role of the subject in Gadamer's hermeneutics. This role is notoriously difficult to define: due to his criticism of traditional metaphysics, Gadamer refers to the subject only in a negative way. It is not given any constitutive role with respect to language, art, or history. However, hermeneutic experience has to involve the subject in a more or less active way: without the subject, understanding and the dialogue with others could not happen at all. The paper traces the role of the subject in the phenomenon of openness, which requires receptivity toward the meaning of other persons or texts. Openness, however, cannot be captured as such. A more explicit form of subjectivity can be seen in negativity, which for Gadamer is a necessary aspect of experience. Finally, the paper refers to his interpretation of Plato's dialectic, which could have served as a model for the way the subject educates herself to become open.